The longevity of two types of cereal carriers for rodenticide baits under adverse environmental conditions - Blažić, Tanja; Živković, Mirko; Stojnić, Bojan; Jokić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
The protection of quality and safety of stored products requires adequate andregular measures of protection from harmful rodents. Poisonous baits in a variety offormulations, primarily those based on cereals, are the most widely applied method ofrodent control. Providing rodenticide baits that are durable over extended periods of time under adverse environmental conditions is an evident challenge for successful rodent control.The present study focused on examining the effects of particle size of maize- andwheat-based rodenticide bait carriers on bait longevity under unfavourable environmental conditions. Maize and wheat grain fractions with particle sizes 2 mm were kept in a climate chamber for 33 days at temperature varying from 30-35 C˚ and humidity from 90-95%. Baits containing different grain fractions, and supplemented with 1% sorbic acid, were tested for mold development. The same grain fractions without the preservative were used as control baits. Test and control baits were exposed to identical environmental conditions in the climate chamber over the same time period.Mold development on preservative-free baits was considerably faster and moreintensive, compared to baits that contained sorbic acid. Initial signs of mold development on control baits were observed as early as on the third day of testing. Carrier type and fraction size affected mold development significantly. Regarding maize-based baits, mold development was more intestive on grain fractions >1.25 mm, compared to wheat-based grain which enabled more intensive development of mold on fractions with particle size
Keywords: rodenticide; bait carrier; mold; wheat; maize; cereals